2021
DOI: 10.1111/imr.12987
|View full text |Cite
|
Sign up to set email alerts
|

Stromal cells in tertiary lymphoid structures: Architects of autoimmunity

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 110 publications
0
23
0
Order By: Relevance
“…This vMIP-II-based PET nanoprobe, known as 64 Cu-DOTA-vMIP-II, was revealed to be targeting endothelial CXCR4 in Apoe −/− mice. In addition, studies with 64 Cu-DOTA-vMIP-II demonstrated an increased CXCR4 expression on plaque margins experiencing a high degree of endothelial dysfunction, thus exposing this tracer as a diagnostic tool for injuries to the endothelium [171]. Other chemokine receptors exploited for imaging of atherosclerotic lesions include CCR5 and CCR2 [172].…”
Section: Imaging As a Diagnostic Tool In Atherosclerosismentioning
confidence: 99%
See 3 more Smart Citations
“…This vMIP-II-based PET nanoprobe, known as 64 Cu-DOTA-vMIP-II, was revealed to be targeting endothelial CXCR4 in Apoe −/− mice. In addition, studies with 64 Cu-DOTA-vMIP-II demonstrated an increased CXCR4 expression on plaque margins experiencing a high degree of endothelial dysfunction, thus exposing this tracer as a diagnostic tool for injuries to the endothelium [171]. Other chemokine receptors exploited for imaging of atherosclerotic lesions include CCR5 and CCR2 [172].…”
Section: Imaging As a Diagnostic Tool In Atherosclerosismentioning
confidence: 99%
“…Besides the above described pathways, chemokines and chemokine receptors also play an important role in atherosclerosis development on other fronts. Under chronic inflammatory conditions, resident stromal mesenchymal cells (MSCs) are activated by proinflammatory molecules, including IL-17, IL-23, LTα 1 β 2 , TNFα, and chemokines, including CCL2, CCL3, CXCL9, CXCL10, and CXCL11 [64][65][66][67]. These molecules are produced by lymphotoxinα1β2-expressing hematopoietic lymphoid tissue inducer (LTi) cells [68].…”
Section: Initiation Of Atherosclerosismentioning
confidence: 99%
See 2 more Smart Citations
“…Even during development, TLS stroma presents a large degree of plasticity (Barone et al, 2016). Early anlagen mesenchyme can differentiate upon specific stimuli into diverse and highly specialized stroma, which then creates functional micro domains within the TLS (Asam et al, 2021). TLS non-vascular stroma is largely represented by fibroblastic reticular cells (FRC), a fine network of canaliculi forming fibroblasts that display unique functional properties, including the ability to support the dramatic anatomical remodelling required to adapt TLS to the influx occurring in response to antigen stimulation (Perez-Shibayama et al, 2019).…”
Section: Stromal Cell Composition and Architecture In Tertiary Lympho...mentioning
confidence: 99%